PENGARUH DOSIS PUPUK ORGANIK CAIR DAN FOSFOR TERHADAP JUMLAH DAUN DAN BERAT BRANGKASAN SEGAR TANAMAN SAWI (Brassica Juncea L.) - Didik Dwi Ardiyanto; Veri Dwi Arum Putri Serang; Adi Prasetyo; Haryuni Haryuni (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2016)
The study effect of phosphorus fertilizer dosage and liquid organic fertilizer to total weight stover Fresh leaves and mustard plant (Brassica juncea L.) aims to determine the dosage of liquid organic fertilizer, phosphorus and interaction on the number and weight of stover fresh leaf mustard. This study uses a randomized complete design (RAKL), with two combination treatments, P0,P1,P2 (0,3,6) organic liquid fertilizer and F0,F1,F2,F3 (0,5,10,15) g of phosphorus fertilizer, so we get twelve combined treatment and repeated three times repetition. The data obtained were analyzed using analysis of variance followed by a further test DMRT if significantly different treatment. The results showed that treatment of liquid organic fertilizer and phosphorus fertilizer significantly different at the observation parameter is the number of leaf mustard plants treated with 6ml organic liquid fertilizer and phosphorus fertilizer 15 g, while the weight parameter fresh stover mustard plants was not significantly different among all treatments. The treatment of liquid organic fertilizer and phosphorus fertilizer best on the number and weight of stover fresh leaves of mustard plants obtained from the combined treatment 6 ml organik liquid fertilizer and phosphorus fertilizer 15 g.